A companion to the twentieth-century Spanish novel - Altisent, Marta, 1950- (Colección Támesis. Monografías, 2008)
This collection of studies by 18 prominent theorists and critics offers a diverse panorama of the modern Spanish novel seen through the prism of Spain's recent political, cultural and ideological history.